Nusyuz Suami dalam Hukum Islam : Analisis Dampak terhadap Kehidupan Keluarga - Andi Silva Quadsajul; Rihan Dwi Putri; Nur Ramadhani; Kurniati Kurniati (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
Nusyūz is usually defined as the wife's disobedience to her husband or vice versa. A wife can be considered nusyūz if she does not carry out her obligations or does not fulfill the rights that should be obtained by the husband and vice versa. The purpose of the study is to explore and analyze the impact of nusyūz committed by the husband on the harmony of household relations and on the family relationship of the married couple. The research method used is a library research method using a quantitative approach. The results show that husband's nusyuz, which is often overlooked in the context of Islamic law, has a significant impact on the relationship between the husband and wife's family. Nusyuz does not only refer to the wife's defiance, but also includes the husband's behavior that does not fulfill his obligations in the household, such as providing proper maintenance, protection, and education for his wife and children. From the analysis conducted, it was found that the husband's nusyuz behavior can cause dissatisfaction in the marriage relationship, leading to conflict between the two families. This injustice is often exacerbated by a patriarchal culture that considers that only wives can be considered nusyuz, thus ignoring the responsibilities of husbands. The psychological impact of the husband's nusyuz is also very detrimental, where the wife and children can be traumatized, both emotionally and physically. This research emphasizes the importance of understanding rights and obligations in Islam, the application of religious teachings, and open communication between spouses to prevent and overcome the problem of nusyuz.